Control of Palmer Amaranth in Agronomic Crops - Jason Ferrell; Barry Brecke; Clyde Smith (EDIS)
SS-AGR-338, a 5-page fact sheet by J. Ferrell, B. Brecke, and C. Smith, provides producers with examples of diverse program approaches for managing Palmer amaranth in corn, cotton, peanut, and soybean. Published by the UF Department of Agronomy, December 2010.